Caused Anxiety and Coping Strategies among Nursing Staff during COVID-19 Outbreak: A Systematic Review - Grispenjas Sumartono Mahira Putra; Nursalam Nursalam; Yuni Sufyanti Arief (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: Coronavirus disease (COVID-19) pandemic has a significant impact on health services and a major psychological challenge for nurses. The aimed of this review was to explore anxiety and coping mechanisms of nurses who provide care to COVID-19 patients. Methods: Search strategies were developed for the Scopus, CINAHL, Lancet, Sage and ProQuest database. The data sources were limited to articles published from 2019-2020. MeSH terms were combined with Boolean operators and used to search the databases. The study quality of each article was determined based on the quality analysis of the JBI guidelines and the study evaluation used PRISMA checklist. Review process; the titles and abstracts of the identified articles, general and specific characteristics from eligible articles were extracted and the quality of included trials were appraised by using a risk of bias assessment tool. Results: The 25 articles provided data on 145 subjects that were randomly allocated to anxiety and coping. The results of this study are six studies (24%) showing the clinical manifestations of nurse anxiety, ten studies (40%) nurse coping mechanism, and nine studies (36%) causes of nurse anxiety. The results of the assessment of each study selected using the JBI Guidelines show that all studies score above 50%, which means it can be used as a reference for systematic review. Efforts to reduce anxiety can be done by implementing strict measures and protections to prevent contracting the COVID-19 virus. Conclusion: This review suggests that the nurse coping mechanism is formed through the guarantee of protection as a health worker that must be fulfilled properly. Hospitals and professional organizations have an important role in supporting this implementation.